Molecular properties of interfaces relevant for clathrate hydrate agglomeration. (September 2019) - Striolo, Alberto; Phan, Anh; Walsh, Matthew R
Graphical abstract: Abstract : Clathrate hydrates of natural gases show promise for energy in regions traditionally poor of fossil fuels, suggest the possibility of mitigating the atmospheric impact of hydrocarbon consumption via CO 2 sequestration, could advance high-tech applications to address global challenges, including the water-energy nexus, and can lead to significant economic loss and potential safety hazards when they form in oil and gas pipelines. This focused review is motivated by several recent contributions, which demonstrate how atomistic and coarse-grained simulations have become a useful tool. The examples provided suggest the time is right to take advantage of the enhanced understanding provided by simulations, to couple them with experiments that could help design new chemicals for managing hydrate formation in pipelines, for designing chemical processes and additives to advance high-tech applications such as water desalination and natural gas storage, and perhaps also for the production of methane from geological hydrate deposits with simultaneous carbon dioxide sequestration.